Measurement of Iris Thickness at Different Regions in Healthy Chinese Adults. (11th May 2021) - Li, Qingchen; Zong, Yuan; Wen, Huiming; Yu, Jian; Zhou, Changbo; Jiang, Chunhui; Liu, Guangxing; Sun, Xinghuai
Abstract : Purpose . To study the variation of iris thicknesses in different regions and explore the possible correlations with age and gender. Methods . Healthy Chinese adults were recruited; the anterior segment of their eyes was imaged by swept-source optical coherence tomography (SS-OCT). The horizontal scan of the right eye was selected, and the thicknesses of both the nasal and temporal irises were measured at 199 evenly spaced points. Results . A total of 233 subjects with an average age of 36.79 ± 10.04 years (range 19 to 62) were included in the final analysis. The mean iris thicknesses of the temporal and nasal sides were 364.79 ± 47.58  μ m and 372.44 ± 43.75  μ m, respectively. The mean nasal iris thickness was positively correlated with age ( β  = 0.9  μ m/year; P  = 0.002), but the temporal one was not ( β  = 0.077  μ m/year; P  = 0.806). At 139 points of the nasal iris and 146 points of the temporal iris, the iris thickness was significantly correlated with age (P  < 0.05). The thicknesses of the peripheral and pupillary parts were positively correlated with age, while the middle part was negatively correlated with age. No significant difference was observed in the mean iris thickness between genders (temporal: t  = 1.597, P  = 0.112; nasal: t  = 1.870, P  = 0.063), but females had a thicker iris than males at 50 points in the temporal side and 49 points in the nasal side (P  < 0.05); no point in males was observed to have thicker iris compared to females. Conclusion . Using SS-OCT and the novel method, thicknesses of the iris at different regions were measured. The thicknesses of the peripheral and pupillary irises increase with age, while the thicknesses of the middle part decrease.